Autopercepción y autorregulación de la calidad de vida del estudiantado de escuelas primarias beneficiarios de un programa social en Chile (Investigaciones) - Burgos Gallegos, Carlos (2025)
Studies on the self-perception and self-regulation of Chilean students are relevant for improvement actions inside and outside the classroom. However, research has not delved into the role of social programs in the mental and psychosocial health of students. Therefore, this research analyzed the risk and protective factors associated with children’s mental health from the evaluation of psychosocial risk, emotional self-regulation and self-perceived quality of life in students benefiting from a social program of JUNAEB, Chile. The research has a correlational design with a cross-sectional scope in which 528 elementary school students participated. An observation instrument and pediatric questionnaires on health and well-being of children and adolescents were used. The results obtained after applying Pearson’s R technique showed a highly significant negative relationship between the variables of psychosocial risk and self-perceived quality of life. Likewise, there was a positive relationship between the independent variables of the study.